Who Has the Rights to Define Antisemitism? - Gunawan Putri, Ferbyani (Jurnal Hubungan Internasional, 2025)
This paper demonstrates how "antisemitism" is used to stifle criticism of Israel. The International Holocaust Remembrance Alliance (IHRA) constructs a dimension of Israel's national identity and history that claims the state's existence while advancing its agenda amidst their human rights controversies. Israeli contribution  to develop a platform offered by the IHRA to assess and consider others behavior. The perception of antisemitism promoted by Israel is rejected by numerous countries, institutions, and Jewish foundations. This paper discloses Israeli motives and reviews “the IHRA definition” and The Jerusalem Declaration on Antisemitsm (JDA) response to IHRA’s “a working definition” using a discourse theoretical framework, as we concluded that Israel uses IHRA to shape the global perspective on antisemitism. This has led to debates questioning who has the authority to define "antisemitism" to prevent its misuse. Keywords: Antisemitism; Israel; IHRA; Human Rights.